Analyzing the English translation of the novel ‘Laskar Pelangi’ (The Rainbow Troops) - Burhanuddin Yasin, M.Ed.; Ika Apriani Fata; Husyitiara Husyitiara (Universitas Syiah Kuala, 2018)
Initial studies show that there are some translations of literary works (from Indonesian to English) where the quality of the translation is questionable due to the loss of information, the addition of information, and the skewing of information. This is the main reason why this research was made. In this research we sought to assess the translation classification and quality of the English version of the novel ‘Laskar Pelangi’ (The Rainbow Troops). The translation classification of Falk et al. (2011)was employed. The translation quality was analyzed using the framework by Nababan et al. (2012). The research employed a documentation technique of descriptive qualitative study. The study found that among 3556 (words, phrases and sentences) data there are 1889 data classified as loss of information, 1527 data categorized as addition of information, and 140 data labeled as skewing of information. The translation quality of this novel was found to be less qualified since its accuracy and acceptability were both low and readability was found to be medium. In order to improve the accuracy, acceptability and readability of a translation, the authors suggest that the translator should have both good translation capabilities as well as cultural understanding of both the source language and target language.